Study of Different Concentrations of Sorbitol as a Plasticizer in Producing Gelatin-Based Biodegradable Film from Chicken Claw Waste - Br Padang, Sheila Saharani; Ratna, Ratna; Munawar, Agus Arip (agriTECH, 2024)
An environmentally friendly packaging material that can be used in place of synthetic, non-green plastic packaging is biodegradable film. Therefore, this study aims to determine the effect of sorbitol plasticizer concentrations on the characteristics of biodegradable film produced from chicken claw waste. The treatments applied during the production process consisted of three sorbitol concentrations, including 0.5, 1, and 1.5%, repeated thrice. Characterization of biodegradable film comprised thickness, water content, water solubility, film swelling, mechanical properties, pH, water vapor permeability, oxygen permeability, and degradation tests. Analysis of variance  results showed that the sorbitol concentrations significantly influenced thickness value, but did not affect other characteristics. The best treatment was 0.5% sorbitol which generated thickness of 0.15 mm, WC of 13.97%, WS of 44.72%, swelling of 96.97%, tensile strength of 12.29 MPa, elongation of 22.23%, elasticity 58.53 Mpa, pH 7.5, WVP 9.26 g.m -1 pa -1 hour -1 , OP 1.52 g.m -1 pa -1 , and degradability for 14 days.